Faktor Internal Lemahnya Penguasaan Bahasa Jawa Krama pada Generasi Muda - M. Suryadi M. Suryadi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
This research has purpose to find the internal factor causing the weakness of mastery of krama lexicon in young generation of Java in Semarang City. The low treasury of krama lexicon affects the use of Javanese krama. Research location in urban area of Semarang: Banyumanik and Tlogosari housing. Data were collected using method:observation, note, record and method: participant, interview. Data were analyzed using quantitative and comparative descriptive method.               The research findings that the treasury krama lexicon on the young generation of Java City Semarang are in very weak classification (score 20.8% - 24.4%). Three internal factors cause weakness of mastery of Javanese krama: (1) pattern of formation of lexicon krama: krama andhap and krama inggil. (2) The placement of lexicon krama in starata fine speech: krama lugu, wredha krama, mudha krama. (3) Changes in morphemes (affix) in the process of formation of lexicon krama.